A dopamine D1 receptor agonist improved learning and memory in morphine-treated rats. (2nd December 2018) - Liu, Qiaofeng; Li, Yanxia; Liu, Yang; Zhao, Yanshuang; Li, Xuemei; Zhang, Yiping; Wang, Chenyi; Huang, Wenli; Wang, Xin
ABSTRACT: Objective : The objective of this article is to study the role of the dopamine (DA) D1 receptor in the midbrain periaqueductal grey (PAG) on learning and memory in morphine-addicted rats. Methods : DA D1 receptor agonist SKF81297 and D1 receptor antagonist SCH SCH23390 were administrated into the PAG, respectively, and the learning and memory behavioral changes of morphine addicted rats were detected by water maze. Western blot and immunohistochemistry were used to detect glutamate decarboxylase 67 (GAD67) and tyrosine receptor kinase B (TrkB) in PAG. Results : D1 receptor agonist shortened the latency to platform and increased the number of platform crossings, indicating improved learning and memory ability of morphine addict rat. D1 receptor agonist increased GAD67 expression and decreased TrkB in PAG. Conclusion : (1) The PAG is involved in the learning and memory changes of the addicted rats; (2) the activation of DA D1 receptor will increase the GAD67, reduce the damage to peripheral neurons, and improve the learning and memory of the addicted rats; and (3) D1 receptor agonists further reduced TrkB expression in morphine-addicted rats, whereas TrkB levels deviated from changes in rat behavior.